A Comprehensive and System Review for the Pharmacological Mechanism of Action of Rhein, an Active Anthraquinone Ingredient - Sun, Hao; Luo, Guangwen; Chen, Dahui; Xiang, Zheng (Frontiers in Pharmacology, 2016)
Abstract Rhein is a major medicinal ingredient isolated from several traditional Chinese medicines, including Rheum palmatum L., Aloe barbadensis Miller, Cassia angustifolia Vahl., and Polygonum multiflorum Thunb. Rhein has various pharmacological activities, such as anti-inflammatory, antitumor, antioxidant, antifibrosis, hepatoprotective, and nephroprotective activities. Although more than 100 articles in PubMed are involved in the pharmacological mechanism of action of rhein, only a few focus on the relationship of crosstalk among multiple pharmacological mechanisms. The mechanism of rhein involves multiple pathways which contain close interactions. From the overall perspective, the pathways which are related to the targets of rhein, are initiated by the membrane receptor. Then, MAPK and PI3K-AKT parallel signaling pathways are activated, and several downstream pathways are affected, thereby eventually regulating cell cycle and apoptosis. The therapeutic effect of rhein, as a multitarget molecule, is the synergistic and comprehensive result of the involvement of multiple pathways rather than the blocking or activation of a single signaling pathway. We review the pharmacological mechanisms of action of rhein by consulting literature published in the last 100 years in PubMed. We then summarize these pharmacological mechanisms from a comprehensive, interactive, and crosstalk perspective. In general, the molecular mechanism of action of drug must be understood from a systematic and holistic perspective, which can provide a theoretical basis for precise treatment and rational drug use.